(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the artistic interpretation of the idea of national awakening in early 20th-century Uzbek Jadid literature. In the works of Jadid writers, issues such as enlightenment, the idea of independence, national self-awareness, and social reforms are examined from artistic and aesthetic perspectives. The research employs historical-comparative, typological, hermeneutic, and textual analysis methods. In particular, the artistic expression of the concept of national awakening is revealed through the works of Abdulla Avloniy, Abdurauf Fitrat, Mahmudxo‘ja Behbudiy, and Cho‘lpon. The article provides a scholarly analysis of the ideological and artistic features of Jadid literature and its role in the development of national consciousness